Mechanical bound state in the continuum for optomechanical microresonators - Yuan Chen; Zhen Shen; Xiao Xiong; Chun-Hua Dong; Chang-Ling Zou; Guang-Can Guo (New Journal of Physics, 2016)
Clamping loss limits the quality factor of mechanical mode in the optomechanical resonators supported with the supporting stem. Using the mechanical bound state in the continuum (BIC), we have found that the mechanical clamping loss can be avoided. The mechanical quality factor of a microsphere could be achieved up to 10 ^8 for a specific radius of the stem, which forms a mechanical BIC with the combination of the symmetry protected mechanism and the single resonance mechanism. Such a mechanism is proved to be universal for different geometries and materials, thus can also be generalized to design high quality mechanical resonators.